MODEL PEMBERDAYAAN PEMUDA BERBASIS OLAHRAGA MELALUI TURNAMEN BOLA VOLI KOLABORATIF PADA PROGRAM KULIAH KERJA NYATA DI NAGARI KOTO GADANG ANAM KOTO - Riska Esa Putri; Poppy Baitul Nisa; Muhammad Azhim Fatullah; Sultan Adli; Yoki Mardas; Miftahul Khair (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This community service activity aimed to strengthen social engagement between university students participating in the Community Service Program (KKN) and youth in Nagari Koto Gadang Anam Koto, Tanjung Raya District, Agam Regency through the organization of a volleyball tournament as part of the sports work program. The activity was initiated to provide positive and structured activities that enhance youth participation and social interaction within the village. The implementation employed a participatory approach, with KKN students serving as the main organizing committee in collaboration with local youth throughout all stages, including planning, drawing of lots, match system arrangement, tournament execution, prize distribution, and a fun match session. The results indicated increased youth enthusiasm and participation, improved communication between students and the community, and the development of sportsmanship and solidarity. The involvement of two KKN students in the Koto Gadang village team further strengthened social bonds and collective spirit. The village team achieved second place in the tournament, contributing to higher community motivation. Therefore, a collaboratively organized volleyball tournament can serve as an effective medium for social engagement and youth empowerment within the KKN framework.